PATIENT SATISFACTION AND ITS ASSOCIATION WITH SERVICE QUALITY PERCEPTION IN DIABETES CARE AT KARTASURA COMMUNITY HEALTH CENTER - Putri, Nabila Lutfiana; Umaroh , Ayu Khoirotul (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Enhancing primary health care quality is crucial, particularly when it comes to managing chronic conditions like diabetes mellitus (DM). The purpose of this study is to investigate how patients with diabetes mellitus at the Kartasura Health Center perceive the quality of their services and how satisfied they are with such services. With a cross-sectional design and a quantitative methodology, this study included 50 Prolanis DM subjects chosen by total sampling. The research instrument refers to the five dimensions of SERVQUAL and KKP-2017, which have been tested for validity and reliability. Data were analyzed univariate and bivariate using chi-square tests. The results show that most patients had a good perception of the quality of service, as well as a high level of satisfaction (90%). All aspects of service quality, including tangibles, assurance, responsiveness, empathy, and reliability, were found to be significantly correlated with patient satisfaction (p<0.05). These findings suggest that the better the perception of service quality, the higher the patient satisfaction. In conclusion, the optimal dimension of service quality, both from physical and interpersonal aspects, plays an important role in increasing DM patient satisfaction. Therefore, improving the quality of patient experience-based services needs to be a strategic focus in primary health services.